PENGARUH MOTIVASI UTILITARIAN DAN MOTIVASI HEDONIS TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PENGUNJUNG SPORT STATION BANDA ACEH - Munawwaratun Husna, Permana Honneyta Lubis (Departemen Manajemen, 2019)
Abstract: This study aims to measure Utilitarian Motivation Influence and Hedonic Motivation on Customer Loyalty mediated by Customer Satisfaction in Banda Aceh Sport Station Users. The sample used in this research is the visitor who visited above three times. Data collection equipment used in this research is questionnaire. The sampling technique used is purposive sampling. Partial Least Square (PLS). used as a method of analysis to determine the effect of all the variables involved. Based on the results of PLS analysis, indicates that Utilitarian Motivation influences Customer Loyalty, Hedonis Motivation affects Customer Loyalty, Utilitarian Motivation affects Customer Satisfaction, Hedonic Motivation influences Customer Satisfaction, Customer Satisfaction affects Customer Loyalty, Customer Satisfaction mediates the relationship between Utilitarian Motivation towards Customer Loyalty, Customer Satisfaction mediates the relationship between Hedonist Motivation to Customer Loyalty.Keywords : Utilitarian Motivation, Hedonic Motivation, Customer Loyalty, Customer Satisfaction, Partial Least Square